Plasticity Is Key to Success of Drosophila suzukii (Diptera: Drosophilidae) Invasion. Issue 3 (17th May 2020) - Little, Catherine M; Chapman, Thomas W; Hillier, N Kirk
Abstract: After its initial discovery in California in 2008, Drosophila suzukii Matsumura has become one of the most important invasive agricultural pest insects across climate zones in much of Asia, Europe, North America, and South America. Populations of D. suzukii have demonstrated notable behavioral and physiological plasticity, adapting to diverse environmental and climatic conditions, interspecific competition, novel food sources, and potential predators. This adaptability and plasticity have enabled rapid range expansion and diversified niche use by D. suzukii, making it a species particularly suited to changing habitats and conditions. This article reviews factors and evidence that influence plasticity in D. suzukii and promotes this species' invasiveness.